Pemanfaatan Situs Sejarah di Lingkungan Sekolah untuk Pembelajaran Tematik SD Negeri 1 Dinoyo Berbasis Edutainment - Wahyudi, Deny Yudo; Sapto, Ari; Nafi’ah, Ulfatun; Ayundasari, Lutfiah; Utari, Shela Dwi; Laili, Vita Sabrina Azda; Ananda, Labuda Shofiya (Education & Learning, 2025)
Malang area is one of the strategic areas that holds many cultural remains from the traditional kingdom period (Hindu-Buddhist period). One of them is the yoni site which was found in the area of SD Negeri 1 Dinoyo. In this regard, this article aims to discuss about the use of yoni sites in the school environment as a support for thematic learning at the elementary school. Especially for thematic learning at SD Negeri 1 Dinoyo. This research was conducted with a descriptive qualitative approach. The main topics of discussion in the study include: 1) the potential of Hindu-Buddhist sites in the Malang area, 2) the concept of edutainment learning, and also discusses about 3) the use of edutainment-based historical sites for thematic learning at SD Negeri 1 Dinoyo. So that it can be seen the important role of sites in the school environment (yoni site int the area SD Ngeri 1 Dinoyo) as well as the potential and advantages possessed by the edutainment method in supporting the achievement of thematic learning in elementary schools